Perempuan dan Komunikasi Politik: Strategi Meraih Suara Perempuan di Pemilihan Umum Melalui Metode Gender Trends - Endhar Priyo Utomo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study has the main objective to form a political communication strategy to win the votes of women in general elections by utilizing the Gender Trends method introduced by Barletta. General elections are one of the political constellations that are commonly practiced in a democratic country. The participation of women in the public sphere as well as decision making through the method of general election has a very important role to increase the number of votes that will be obtained by candidates for the election, both presidential and vice-presidential candidates as well as candidates for legislative candidates who are representatives of several parties participating in the Election. Seeing the importance of women's voices, making candidates have to have a strategy to attract sympathy from women voters. This study with the use of the Gender Trends method will help the candidates more or less understand what women voters want. This method is actually the method applied in marketing strategies to attract interest from female customers. However, after simple research, it seems very appropriate when applied in this study. This study is a study with a qualitative approach and utilizes library studies. Based on the results of the study, the formulation of hypotheses capable of increasing the number of voters from the women's side can be classified as follows: a) identification of female voice enhancing factors in the election, b) finding the voice enhancing dimensions of women in elections, and c) finding strategies to win women's votes in elections.